2016
DOI: 10.1016/j.jcv.2016.01.013
|View full text |Cite
|
Sign up to set email alerts
|

Human pegivirus detected in a patient with severe encephalitis using a metagenomic pan-virus array

Abstract: We have used a metagenomic microarray to detect genomic RNA from human pegivirus in serum and cerebrospinal fluid from a patient suffering from severe encephalitis. No other pathogen was detected. HPgV in cerebrospinal fluid during encephalitis has never been reported before and its prevalence in cerebrospinal fluid needs further investigation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 30 publications
0
18
0
Order By: Relevance
“…Furthermore, the association of HPgV with multiple sclerosis could not be established because the study was limited to a single case. In the third study, HPgV was detected in serum and CSF of a patient with a severe form of encephalitis of unclear origin ( 17 ). Of these 3 studies, none included comparison of serum- and CNS-derived virus.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the association of HPgV with multiple sclerosis could not be established because the study was limited to a single case. In the third study, HPgV was detected in serum and CSF of a patient with a severe form of encephalitis of unclear origin ( 17 ). Of these 3 studies, none included comparison of serum- and CNS-derived virus.…”
mentioning
confidence: 99%
“…Three recent case reports described HPgV RNA in the human central nervous system (CNS), demonstrating that the virus can be present in the brain under certain circumstances ( 15 17 ). In the first study, viral sequences were detected postmortem in brain tissue from a patient with multiple sclerosis, not encephalitis ( 15 ).…”
mentioning
confidence: 99%
“…Although it was reported that B19V shows lifelong persistence in the heart,33 its relevance to myocarditis in the present case was suggested because B19V DNA was detected from both serum and myocardium specimens.In RNA sequencing, a large number of HPgV sequence reads were detected from one patient (patient 16). HPgV was initially suspected to be a cause of chronic hepatitis; however, the pathogenicity of HPgV to human remains inconclusive, despite its capacity for persistent viremia 34,35. In addition, astrovirus, tobacco mosaic virus, and peanut stunt virus were detected in RNA sequencing, but viral reads were derived from the single location of each reference genome (data not shown).…”
mentioning
confidence: 99%
“…Human pegivirus has been detected in 1-45% of healthy blood donors worldwide [24]. Detection of this virus in CSF samples from patients with encephalitis through metagenomics sequencing brings questions related to its apparent pathogenicity versus coincidental detection from a leaky blood-brain barrier(BBB) [25]. A recent study used whole genome sequencing of pegivirus virions in samples from CSF and serum in patients with undiagnosed encephalitis [26] and demonstrated divergent sequences suggesting compartmentalisation and potential pathological replication in the CNS.…”
Section: Sequencingmentioning
confidence: 99%